Pelatihan Pembuatan Ransum Ayam KUB pada Kelompok Ternak Kambang Saiyo di Nagari Kambang Barat, Kecamatan Lengayang, Kabupaten Pesisir Selatan - Sepri Reski; Zurmiati Zurmiati; Ridho Kurniawan Rusli (Warta Pengabdian Andalas, 2024)
This activity aims to help the Kambang Saiyo livestock group by providing training on preparing KUB chicken ration formulations using applications. In addition, this activity also aims to train the community to formulate conventional feed ingredients according to procedures. The activity included counseling on feed ingredients that can be used for poultry, especially KUB chickens, nutritional and energy requirements for KUB chickens, and introducing software that can be used to formulate KUB chicken rations. Then, the activity continued with a demonstration of compiling the ration according to the formula. As a result of this activity, the group understood the types of feed ingredients suitable for KUB chickens and the application or valuable software in preparing KUB chicken rations. In conclusion, this activity increased farmers' knowledge and skills in designing application-based KUB chicken ration formulas.